The Cold War : an international history - Painter, David S. (Making of the contemporary world., 1999)
"David Painter provides a compact and analytical study that examines the origins, the course, and the end of the Cold War. His overview is global in perspective and focuses on the interaction of international rivalries and national politics and policies. In addition to the geopolitical rivalry between the United States and the Soviet Union that was at the center of the Cold War, he examines such important issues as changes in the global distribution of power, the dynamics of the arms race, ideological divisions within and among nations, the evolution of the world economy, and the political and economic transformations of the Third World."--Jacket